Characteristics of pediatric interventional drug trials registered between 2015 and 2024 on ClinicalTrials.gov - Zhou, Yinghong; Liu, Zhaoxin; Xu, Ji; Zhang, Ying; Shen, Haiqi; Jiang, Siyu; Shi, Yunyun; Lv, Yinghua; Huang, Jihan (Frontiers in Pediatrics, 2025)
AimThis study comprehensively analyzed the characteristics and development trends of pediatric interventional drug clinical trials registered between 2015 and 2024, with a focus on pharmaceutical characteristics such as dosage form and administration route.MethodsThe ClinicalTrials.gov database was searched to identify trials involving pediatric participants. Interventional trials first posted between 2015 and 2024 were included if they used drugs as interventions and had treatment as the primary purpose.ResultsA total of 2,928 pediatric-only clinical trials were included, with annual registration numbers ranging from 257 to 339, exhibiting a declining trend. Among these, 1,975 (67.5%) enrolled no more than 100 participants, and 153 (5.2%) were restricted to either males or females, with this gender-specific enrollment correlated with disease epidemiology. Mental, behavioral, or neurodevelopmental disorders (319, 10.9%) represented the most studied therapy area, maintaining high proportions consistently across Phases 1–3. The most common dosage forms were liquid (53.3%) and solid (24.0%), and the most frequently reported administration routes were enteral (39.0%) and parenteral (35.6%). Drug formulations and administration routes varied by age group: the use of solid formulations (from 12.1% to 29.1%) and enteral administration (from 22.9% to 42.0%) increased with age, while the use of liquid formulation and parenteral administration declined.ConclusionIn the last ten years, registered pediatric drug trials have either stayed stable or slightly decreased, often featuring small sample sizes and rarely using age-specific formulations. National regulatory bodies should boost policy support to encourage pediatric drug research and improve trial design quality.